A barbárie da reflexão: o alerta de Giambattista Vico sobre os rumos da vida civil - Figueiredo, Marcela Cássia Sousa de Melo Benicio (2020)
This thesis has as its central theme the concern with the direction of civil life, based on the alert made by the Italian philosopher Giambattista Vico (1668-1744) about a barbarism of reflection. Our hypothesis is that the importance of the Viquian alert, made at the end of the seventeenth century, is to make the concern about the hypertrophy of scientific objectivity recurrent in detriment of other dimensions of life that constitute civility. To confirm this hypothesis, we will follow a path that begins with the Viquian intellectual formation, its appeal to the rhetorical tradition, passing through its pedagogical proposal, its civil theology with the relevant role of divine providence and the importance of common sense, until we formulate the genesis of the civil world of nations, comprising the historical tripartition and, finally, with this conceptual basis, we arrive at the discussion about the barbarity of reflection. The Viquian works are relevant, punctually, in each part of this route. We highlight, in the course of this research, the Viquean defence for a close relationship between Philology and Philosophy, that is, between the particular and the universal and, with that, we explain the Viquian concern in the search for the principles and development of the civil world of nations . In this research, the Viquian philosophy helps us in trying to understand the historical cycles that form a society, its values, its customs, its decadence, and possible regenerations. Thus, such a study directs us to look at the importance of an orientation that aims at the formation of a social being. What is worth emphasizing in the investigation, therefore, is the way in which Vico exposes such concepts in his thinking and in what way his project represents something innovative in his time. Finally, this process encourages us to consider the risks that affect the direction of civil life.